2002
DOI: 10.1136/vr.150.21.655
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of measurements of the conductivity of quarter milk samples for the early diagnosis of mastitis

Abstract: Measurements of the conductivity of quarter milk samples were made in 31 cows in a 70-cow herd in southeast England, for a period of 15 weeks. Over this period, 42 per cent of cow-weeks and 20 per cent of quarter-weeks had an increase in quarter milk conductivity of 10 per cent of more compared with the mean conductivity of the previous 14 milkings. Fourteen per cent of quarter-weeks had an increase in conductivity of 15 per cent or more. The geometric mean somatic cell count (cell count) was higher in quarter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…An EC is a useful parameter for evaluating milk quality and has been introduced as an indicator of udder health (Biggadike et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An EC is a useful parameter for evaluating milk quality and has been introduced as an indicator of udder health (Biggadike et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mastitis causes changes in the conductivity of milk, by damaging mammary epithelia and thereby altering the balance of sodium, potassium and chloride ions (Kitchen 1981). A rise in sodium and chloride contents results in increased electrical conductivity (EC) in the milk (Biggadike et al . 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Eckersall and others (2001) were the first to demonstrate significant increases in their concentrations in the milk of cows with clinical mastitis. Their results suggested that serum amyloid A was produced locally in the mammary gland, potentially making it an early, specific marker of mastitis, which might prove more sensitive than a bacteriological examination and less influenced by the physiological stage of the cow than the somatic cell count or the electrical conductivity of the milk (Sheldrake and others 1983, Biggadike and others 2002). However, it is still not known whether inflammatory processes occurring outside the mammary gland influence its concentration in milk.…”
Section: Methodsmentioning
confidence: 99%
“…Most studied methods for cow mastitis detection using EC are based on processing data from EC sensors located at short milk tube or claw (also at gland level) and applying algorithms that consider the comparison of gland EC with the moving average of previous milkings (Lansberger et al 1994;Mele et al 2001;Biggadike et al 2002;Zecconi et al 2004;Cavero et al 2007; Kamphuis et al 2008a) and the comparison of EC of collateral glands (Maatje et al 1992(Maatje et al , 1997Lien et al 2005). In all these studies, specificity (SPEC) was around 90%, but sensitivity (SENS) was lower (different results were obtained depending on the study and type of mastitis: clinical, subclinical or somatic cell count (SCC) increases, from 25 to 89%).…”
Section: Introductionmentioning
confidence: 99%